2006
DOI: 10.1097/01.mlg.0000240908.88759.fe
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Follow‐up of Hearing Loss in Children and Young Adults With Enlarged Vestibular Aqueducts: Relationship to Radiologic Findings and Pendred Syndrome Diagnosis

Abstract: Patients with EVAs should be advised to avoid known trigger factors for sudden drops in hearing (e.g., minor head trauma). A diagnosis of PS may be associated with a worse audiologic prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
74
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(81 citation statements)
references
References 27 publications
5
74
0
2
Order By: Relevance
“…An air-bone gap at the low frequencies has been reported to occur in 15% to 100% of patients with LVAS by various authors. [1][2][3][4][5][6][7][8][9][10] The mechanism of an air-bone gap in LVAS remains unclear. Some investigators have suspected fixation, loosening, or discontinuity of the ossicles.…”
Section: Introductionmentioning
confidence: 99%
“…An air-bone gap at the low frequencies has been reported to occur in 15% to 100% of patients with LVAS by various authors. [1][2][3][4][5][6][7][8][9][10] The mechanism of an air-bone gap in LVAS remains unclear. Some investigators have suspected fixation, loosening, or discontinuity of the ossicles.…”
Section: Introductionmentioning
confidence: 99%
“…21 Our data concur with previous studies in which measures of signal intensity within the endolymphatic sac did not shown a correlation with the degree of hearing loss. 5 We were particularly interested in the possibility that the presence and occasional rupture of a compartment, with reflux of accumulated debris and metabolites, could be associated with the well-described episodes of sudden or fluctuating hearing loss and vertigo. Sudden hearing loss may be triggered by coryzal illness, trauma, exercise and aeroplane travel, 5 and associated variations in pressure could result in septation rupture and fluid leakage.…”
Section: Discussionmentioning
confidence: 99%
“…endolymphatic sac size, endolymphatic sac T2-weighted magnetic resonance imaging (MRI) signal, and associated labyrinthine anomalies) with patients' audiological findings; however, results have been inconsistent. 4,5,8,9 There have also been limited reports of the presence of internal compartments within large endolymphatic sacs, demonstrated on MRI scans. 4,10,11 However, their significance and their impact on our understanding of the associated hearing loss have not been systematically explored.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations